A preliminary assessment of the initial compression power requirement in CO2 pipeline “Carbon Capture and Storage (CCS) technologies" - El-Suleiman, Abdussalam; Anosike, Nnamdi Benedict; Pilidis, Pericles (MDPI, 2016)
CO2 captured from fossil-fueled power generation plants is said to be economically transported via pipelines over long distances. The CO2 must be compressed to pipeline specifications using compressors and pumps that are driven by gas turbine (GT) or other prime movers. This paper presents the evaluation of actual work transfer or required prime power by modeling the governing equations of compression using the Peng–Robinson equation of state (PR-EOS). A computer code was developed to carry out the modeling and subsequent simulation of the compression power requirement. The simulation of prime mover power was carried out for different technology (head per stage) of the compressor ranging from 10-staged compression to double stage compression. The results show that the current technology of the centrifugal compressor could require as much as 23MW of prime mover power to compress 1.5 million tonnes per year of CO2—a projected equivalent CO2 released from a 530MW combined cycle gas turbine (CCGT) power generation plant.
Keywords: CO2; Pipeline; Prime mover; CO2 compression; Combined cycle gas turbine; CCGT